QUALITATIVE AND QUANTITATIVE PHYTOCHEMICAL ANALYSIS OF ENDOPHYTIC FUNGI (EF8; ASPERGILLUS SP.3) ISOLATED FROM BOERHAVIA DIFFUSA L., STEM. - THAKUR, DEEPENDRA; SAHANI, KAMANA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present investigation was to find phytochemical constituents of endophytic fungi Aspergillus sp.3 isolated from Boerhavia diffusa L. stem. Methods: Both qualitative and quantitative phytochemical analysis was performed. Results: In the present investigation, endophytic fungi was isolated from the medicinal plant B. diffusa L. The qualitative and quantitative phytochemical analysis was performed from the endophytic fungi Aspergillus sp.3 which showed the presence of phenol, flavonoids, alkaloids, steroids, and terpenoids, 11.66±0.577, 17.66±0.577, 1.746±0.0057, 0.446±0.0057, and 9.746±0.0057 (μg of standard/mg of extract), respectively. Conclusion: Hence, the endophytic fungi isolated from B. diffusa L. could be regarded as good sources of bioactive compounds for drug formulations.